2020
DOI: 10.1101/2020.10.06.328724
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating genetic nurture with summary statistics of multi-generational genome-wide association studies

Abstract: Marginal effect estimates in genome-wide association studies (GWAS) are mixtures of direct and indirect genetic effects. Existing methods to dissect these effects require family-based, individual-level genetic and phenotypic data with large samples, which is difficult to obtain in practice. Here, we propose a novel statistical framework to estimate direct and indirect genetic effects using summary statistics from GWAS conducted on own and offspring phenotypes. Applied to birth weight, our method showed nearly … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Recall that Sanjak et al (2018) reported inconsistent findings between reproductive success and age at menarche (positive) and age at menopause (negative), which the authors label as “less explicable” than other results 10 . Similar to earlier findings 6,8 , we show correlations with EA and cognition, but extend this finding by showing these results are driven by direct-EA component and not by indirect-EA component (i.e., genetic nurture) using methods in Wu et al (2020) 42 . The difference in these findings suggest a broader need for caution when examining the genetic correlation findings, as we cannot decouple parental and child genetics in these results.…”
Section: Resultssupporting
confidence: 91%
“…Recall that Sanjak et al (2018) reported inconsistent findings between reproductive success and age at menarche (positive) and age at menopause (negative), which the authors label as “less explicable” than other results 10 . Similar to earlier findings 6,8 , we show correlations with EA and cognition, but extend this finding by showing these results are driven by direct-EA component and not by indirect-EA component (i.e., genetic nurture) using methods in Wu et al (2020) 42 . The difference in these findings suggest a broader need for caution when examining the genetic correlation findings, as we cannot decouple parental and child genetics in these results.…”
Section: Resultssupporting
confidence: 91%
“…Both previous studies observed significant genetic correlations for the number of children between men and women (Barban and colleagues 23 : r g =0.97, SE=0.095; Mathieson and colleagues 29 : r g =0.74, 95%CI=0.66-0.82), which our findings from the conditional analysis are consistent with (r g =0.871, SE=0.023). We also identified a strong negative genetic correlation between both male/female fertility and sibling effects; this is likely to be due to a technical artefact of the analyses as described by Wu and colleagues 30 . We replicate the negative genetic correlation between years of education and fertility described in Barban et al 23 .…”
Section: Discussionmentioning
confidence: 53%
“…One efficient way to control for SES-related gene-environment correlations is by conducting within family GWAS analyses. [23][24][25] Within family analyses, however, do not allow us to identify and study the specific source of gene-environment correlations, where our analyses do. In addition, while family-datasets are growing, large sample sizes of genotyped families are harder to attain, which results in less powerful within-family GWASs with noisier estimates of genetic effects (Figure 4).…”
Section: Discussionmentioning
confidence: 90%